METHODOLOGY AND STRATEGIES FOR MODERNIZATION OF THE LANGUAGE EDUCATIONAL POLICY IN THE CONTEXT OF SOCIO-CULTURAL TRADITIONS (Revista Inclusiones, 2020)
This article is devoted to the study of the methodology and strategies for the modernization of education in the Russian and foreign sociocultural traditions. The modernization of the national education system in the Russian Federation actualizes the need for the analysis of socio-educational transformations in the mid-20th and early 21st centuries. This research has important theoretical and practical significance for determining the strategy for the comprehensive modernization of Russian and some foreign educational systems. The methodological significance of the study lies in the need for analytical reconstruction of the multidimensional modernization and educational reforms. It is important to trace the chronological and analytical correlation of the evolution of Russian and international studies of educational systems at this historical stage in the framework of the sociocultural development.